Pengaruh Kualitas Pegawai Dan Komitmen Organisasi Terhadap Kinerja Pegawai Bagian Sekretariat Pada Dinas Pemadam Kebakaran Dan Penanggulangan Bencana Kabupaten Kutai Kartanegara - Adawiyah, Raudatul (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
This research was to analyze The Influence Of Quality Of Employee And Organizational Commitment To Employee Performance Of Secretariat Fire And Disaster Prevention Office Of Kutai Kartanegara Regency. The results showed that the independent variables have a significant relationship or employee performance variable influenced by variable Quality Employees (X1) and Organizational Commitment (X2). Then the first hypothesis stating that “Variable Quality Employees And Organizational Commitment Affects Employee Performance Secretariat Field At Fire Department And Disaster Mitigation Kutai Kartanegara Regency